2015
DOI: 10.1039/c5ra22968e
|View full text |Cite
|
Sign up to set email alerts
|

Complicated synergistic effects between metal–π interaction and halogen bonding involving MCCX

Abstract: Complicated synergistic effects have been found between metal–π interaction and halogen bond in the complexes FCCF⋯MCCX⋯NCH (M = Li, Cu, Ag, and Au; X = Cl, Br, and I).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…21 In constructing crystal materials, more than one interaction is present, thus cooperative effect occurs, which is one of important properties of noncovalent interactions. It was demonstrated that halogen bonds exhibit cooperative effects with themselves or other interactions, [26][27][28][29][30][31][32][33][34][35] through which the strength of halogen bonds is modulated.…”
Section: Introductionmentioning
confidence: 99%
“…21 In constructing crystal materials, more than one interaction is present, thus cooperative effect occurs, which is one of important properties of noncovalent interactions. It was demonstrated that halogen bonds exhibit cooperative effects with themselves or other interactions, [26][27][28][29][30][31][32][33][34][35] through which the strength of halogen bonds is modulated.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the physical origins of noncovalent interactions is an important task for EDA methods. GKS‐EDA and LMO‐EDA have been used to analyze various noncovalent interactions, including hydrogen bond, halogen bond, chalcogen bond, tetrel bond, pnicogen bond, π‐π stacking, cation⋯π, anion⋯π, XH⋯π (X = C, N, or O), and cooperative effects . Here we illustrate several representative applications for hydrogen bonds, halogen bonds and π‐π stacking, which show the diversity of physical origins in various noncovalent interactions.…”
Section: Applicationsmentioning
confidence: 99%
“…1 There are some well-known methodologies for the evaluation of the cooperativity of noncovalent bonds and the calculation of related cooperative energies. The following equations have been frequently used for the evaluation of the cooperativity of coinage-metal bonds with other types of interactions 2–13 and also that of intermolecular noncovalent bonds, especially those including hydrogen bonds, 14–25 dihydrogen bonds, 26–28 beryllium bonds, 29,30 lithium bonds, 31–34 lithium–π, 35 halogen bonds, 36–48 chalcogen bonds, 49–51 pnicogen bonds, 52–56 cation–π interactions, 57–60 anion–π interactions, 61–63 π⋯π interactions, 64 σ -hole 65,66 and π -hole 67–70 interactions in ternary systems. Δ ABC = IE total ABC − (IE ABC A–B + IE ABC B–C + IE ABC A–C ) E coop = SE ABC − (SE AB + SE BC + SE ABC AC ) E coop = SE ABC − (SE AB + SE BC )In the above equations, Δ ABC and E coop correspond to the three-body term 71–77 and cooperative energy, respectively. The term IE total ABC is used for the value of the total interaction energy of the ABC system, and the terms IE ABC AB , IE ABC BC and IE ABC AC are used for pairwise interaction energies in the structure of the ABC system.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are some wellknown methodologies for the evaluation of the cooperativity of noncovalent bonds and the calculation of related cooperative energies. The following equations have been frequently used for the evaluation of the cooperativity of coinage-metal bonds with other types of interactions [2][3][4][5][6][7][8][9][10][11][12][13] and also that of intermolecular noncovalent bonds, especially those including hydrogen bonds, [14][15][16][17][18][19][20][21][22][23][24][25] dihydrogen bonds, [26][27][28] beryllium bonds, 29,30 lithium bonds, [31][32][33][34] lithium-p, 35 halogen bonds, [36][37][38][39][40][41][42][43][44][45][46][47][48] chal...…”
Section: Introductionmentioning
confidence: 99%